The Integration and Innovation of Information Technology in Revolutionary Educational Strategies in the Digital Era - Muhammad Rinov Cuhanazriansyah; Boedy Irhadtanto; Ratih Tantriasari; Tirza Ananda Yulia Putri (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This study aims to explore the integration and innovation of information technology within educational strategies in the digital era, focusing on its impact on student engagement and the challenges encountered during implementation. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 35 students and 10 faculty members, while qualitative data were obtained through in-depth interviews with 15 students and 5 faculty members. The findings reveal that 80% of respondents use technology in their learning almost daily, and 79% believe that technology is highly effective in enhancing their understanding of the material. Additionally, 83% of respondents feel more engaged when utilizing technology. However, barriers such as limited internet access (45%) and inadequate devices (33%) remain significant challenges. The conclusion of this research emphasizes that, although the integration of technology in education offers numerous benefits, existing challenges must be addressed to maximize the potential of technology in improving educational quality. Recommendations for decision-makers include enhancing technological infrastructure and providing training for educators to optimize the use of technology in the learning process. This study is expected to provide insights for the development of more effective and innovative educational strategies in the digital era.